歯肉病変より診断し得たWegener肉芽腫の1例 - 西久保, 周一; 小野田, 紀生; 河地, 誉; 田村, 英俊; 大金, 覚; 東郷, 拓也 (日本口腔外科学会雑誌, 2013)
Wegener's granulomatosis is a rare multi-system disease characterized by necrotic and granulomatous changes of the upper or lower respiratory tract and segmental necrotizing glomerulonephritis. Wegener's granulomatosis is considered a type of PR-3-ANCA-associated vasculitis. This disease is defined as an autoimmune disease. Only 2% of all patients develop Wegener's granulomatosis in the oral cavity, which is characterized by strawberry gums. We describe a patient with a painful gum ulcer in whom Wegener's granulomatosis was diagnosed at an early stage on the basis of clinical findings of internal medicine and gingival biopsy in collaboration with other departments.